Student Engagement in a Gamified Physics Course (Proceedings of the International Conference on Future of Education, 2019)
This study investigated the students’ behavioral, emotional, and cognitive engagement in a gamified Physics course. The participants in the study are engineering students from a state university in Manila, Philippines taking up a summer class in Electromagnetics. The course was gamified by incorporating various games elements which include experience points (XP), leaderboard, quests, events, challenges, achievements, leaderboards, and power-ups. The engagement of students was measured using the Student Engagement Measure (SEM). Mean scores, standard deviations, and correlation coefficients were calculated. The results revealed a high level of behavioral, emotional, and cognitive engagement of students in the gamified physics course. The three subscales were also found to be significantly correlated with each other. Furthermore, the journal and interview transcripts revealed that students exhibited active participation, established good relationships with others and perceived the course to be fun, enjoyable and exciting, and exerted more effort and work beyond what is required in the gamified course.
Keywords: gamification; student engagement; physics